E-045 Intravascular ultrasound for evaluating venous sinus stenosis in patients with pseudotumor cerebri/Idiopathic intracranial hypertension. (22nd July 2019) - Nicholson, A; Woods, C; Taylor, S; Guilliams, E; Cuoco, J; Klein, B; Summers, D; Witcher, M; Marvin, E; Entwistle, J
Abstract : Introduction/Purpose: Imaging and pressure readings in patients with pseudotumor cerebri (PTC)/idiopathic intracranial hypertension (IIH) are traditionally done using magnetic resonance imaging (MRI) and minimally invasive catheter-based manometry. These measurements are important to rule out other diagnoses, deciding where to place a stent, and evaluating patients post-stent. However, the intravascular ultrasound (IVUS) is a newer technology that needs to be further evaluated for its potential as a replacement for these current methods. IVUS can be used to both measure the degree of stenosis of the vessel as well as the pressure gradient through its functional flow reserve (FFR) measurement. By comparing the measurements from IVUS to those from both MRI and manometry, the use of this newer technology in diagnosing and treating IIH can be further understood. Materials and methods: This study is a retrospective chart review consisting of 10 consecutive patients with IIH who underwent venous sinus stenting at our institution. All patients had measurements taken via MRI, manometry, FFR pressure measurements and IVUS. We plan to compare the IVUS measurements to both MRI and pressure measurements to assess the degree of stenosis in these patients. Post-stenting follow up data is available between 3–9 months. Results: Initial analysis demonstrates a strong correlation between venous stenosis seen on IVUS and pressure gradients. This holds up even in patients with little to no stenosis seen on MRI. Final statistical analysis is in process and will be completed in time for the conference. Conclusion: As stenting becomes a more popular course of treatment for IIH patients, it is important that the technology used for these procedures is accurate. This study will help expand the literature surrounding the use of IVUS as a diagnostic tool for patients with IIH. Disclosures: A. Nicholson: None. C. Woods: None. S. Taylor: None. E. Guilliams: None. J. Cuoco: None. B. Klein: None. D. Summers: None. M. Witcher: None. E. Marvin: None. J. Entwistle: None.